2009
DOI: 10.1080/01639370902737315
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Use of Metadata for Digital Learning Objects in University Institutional Repositories (MODERI)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…The success of ROER in the UK might be due to the considerable funding provided for OER projects by the Joint Information Systems Committee (JISC). This pattern varies in other studies (Bueno - de-la-Fuente et al, 2009), in which the USA was found to be the most common location (28%), followed by Germany and Italy. However, our results might be influenced by the fact that they only focus on higher education ROER.…”
Section: Geographical Origincontrasting
confidence: 48%
See 1 more Smart Citation
“…The success of ROER in the UK might be due to the considerable funding provided for OER projects by the Joint Information Systems Committee (JISC). This pattern varies in other studies (Bueno - de-la-Fuente et al, 2009), in which the USA was found to be the most common location (28%), followed by Germany and Italy. However, our results might be influenced by the fact that they only focus on higher education ROER.…”
Section: Geographical Origincontrasting
confidence: 48%
“…Regarding educational issues, studies have mainly focused on benefits, challenges, and limitations associated with OER (Wiley et al, 2014), their creation and distribution (open textbooks, repositories, OCW courses and MOOCs), and their important role in open education (Lane & McAndrew, 2010;UNESCO, 2011;OECD, 2015). There are many studies on metadata evaluations of ROER (Bueno-de-la-Fuente, Hernández-Pérez, Rodríguez-Mateos, Méndez-Rodriguez, & Martín-Galán, 2009), but these adopt a formal and technological perspective rather than analyze the educational relevance of ROER (Rodríguez, Dodero & Sánchez-Alonso, 2011;Atenas & Havemann, 2013). Therefore, the current study aims to explore how ROER support teaching and learning, based on educational requirements.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol appears with the Open Archives Initiative published in 1999, whose first public version was in 2001, due to the need to convert files into interoperable files and build information retrieval services from many repositories (Becerril García, Lozano Espinosa, and Molina Espinosa 2016). In that sense, Open Access digital repositories have implemented the OAI protocol as a mechanism to achieve interoperability in the exchange of meta-information with other systems such as the metadata harvesters (Bueno-De-La-Fuente et al 2009). …”
Section: Metadata Management In Digital Repositoriesmentioning
confidence: 99%